An Analysis of the Influence of Independence, Accountability, nd Objectivity on Audit Quality in the Public Accounting Profession in Indonesia - Allya Nathalie Radina S; Ardiansyah Ardiansyah (International Journal Labs, 2026)
Audit quality is a crucial element in maintaining public trust in financial reporting and ensuring the credibility of information used by stakeholders in economic decision-making. However, several audit failures have demonstrated that audit quality remains a significant challenge, particularly when auditors encounter threats to professional judgment, independence, accountability, and objectivity. This study aims to examine and synthesize previous research findings regarding the roles of auditor independence, accountability, and objectivity in improving audit quality within the public accounting profession in Indonesia. This research employed a Systematic Literature Review (SLR) method by analyzing relevant scientific publications obtained from databases, including Google Scholar, Garuda, and SINTA. The selected articles were evaluated based on predetermined inclusion criteria and analyzed using qualitative content analysis to identify research patterns, relationships among variables, and research gaps. The findings indicate that auditor independence is a fundamental factor influencing audit quality because it enables auditors to provide impartial judgments without external pressure or conflicts of interest. Furthermore, accountability encourages auditors to conduct audit procedures carefully and responsibly, while objectivity ensures fairness and neutrality in evaluating audit evidence. The discussion highlights that these three professional attributes complement one another in strengthening audit credibility and stakeholder confidence. This study concludes that improving audit quality requires continuous efforts from auditors, Public Accounting Firms (PAFs), regulators, and professional organizations through ethical enforcement, effective quality control systems, competency development, and the strengthening of professional standards.